2018
DOI: 10.1037/abn0000373
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties with being socially accepted: An experimental study in borderline personality disorder.

Abstract: Anxious preoccupation with real or imagined abandonment is a key feature of borderline personality disorder (BPD). Recent experimental research suggests that patients with BPD do not simply show emotional overreactivity to rejection. Instead, they experience reduced connectedness with others in situations of social inclusion. Resulting consequences of these features on social behavior are not investigated yet. The aim of the present study was to investigate the differential impact of social acceptance and reje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 59 publications
6
42
1
Order By: Relevance
“…Where studies were conducted in similar locations or with similar authors, authors were contacted to identify overlapped samples. Four BPD samples partially overlap (Bungert, Koppe, et al ., ; Bungert, Liebke, et al ., ; Liebke et al ., ; Thome et al ., ). As the authors contacted were not certain of the extent of this, All four are reported in the narrative review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where studies were conducted in similar locations or with similar authors, authors were contacted to identify overlapped samples. Four BPD samples partially overlap (Bungert, Koppe, et al ., ; Bungert, Liebke, et al ., ; Liebke et al ., ; Thome et al ., ). As the authors contacted were not certain of the extent of this, All four are reported in the narrative review.…”
Section: Resultsmentioning
confidence: 99%
“…In non‐clinical samples, RS correlated with BPD features, with variation in effect sizes ( r = .11 to .63). Two studies did not find a significant effect in five different community samples and a clinical sample, though the effect size remained small to moderate ( r = .16 to .35; Brown, ; Liebke et al ., ). Large effect sizes were found in studies of moderate quality; however, quality did not differentiate moderate and small effects.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, it has been measured at a single point in time [32], aggregated across multiple time points [18,33], or restricted to focus on a single phase of trust [17]. To the authors' knowledge, only one study has accounted for trust dissolution and trust restoration by manipulating trustee reciprocity to differentiate between three phases: cooperative reciprocity, where the trustee returned a profit across five consecutive rounds; trust rupture, where the trustee kept the entire investment; and trust repair, where the trustee behaved cooperatively following rupture [18]. Trust was operationalized as the amount transferred by the investor to the trustee for investment, averaged across the aggregated rounds of each phase.…”
Section: Trust and Bpdmentioning
confidence: 99%
“…The evaluation of social signals, in turn, is biased by individual differences in personality traits including rejection sensitivity (RS) – the susceptibility to interpret social cues as signs of rejection (Staebler, Helbing, Rosenbach, & Renneberg, ) – which is relevant for mental health in general, and for BPD in particular (Gao, Assink, Cipriani, & Lin, ). Put another way, individuals with BPD appear to process signals of social acceptance in deviant ways (Liebke et al , ), and they perceive exclusion in a negatively biased way and feel more readily excluded than healthy controls (Renneberg et al , ). The association between RS and BPD has been reported at a medium effect size (pooled r = .413) in a meta‐analysis (Gao et al , ), and a recent overview has shown that emotional abuse and neglect were linked to RS (Foxhall et al , ).…”
Section: Nonverbal Synchronymentioning
confidence: 99%